2020
DOI: 10.1016/j.psyneuen.2019.104552
|View full text |Cite|
|
Sign up to set email alerts
|

Exogenous testosterone increases status-seeking motivation in men with unstable low social status

Abstract: Testosterone is associated with status-seeking behaviors such as competition, which may depend on whether one wins or loses status, but also on the stability of one's status. We examined (1) to what extent testosterone administration affects competition behavior in repeated social contests in men with high or low rank, and (2), whether this relationship is moderated by hierarchy stability, as predicted by the status instability hypothesis. Using a real effort-based design in healthy male participants (N = 173 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 58 publications
6
37
1
Order By: Relevance
“…In the current study, individuals with high androgen receptor sensitivity to testosterone (i.e., low AR(CAG)-repeat length), showed that testosterone (vs. placebo) increased motivation to compete when the competition progressed in those who had an unstable low status as well as in those who had a stable high status. A recent study in males demonstrated testosterone to promote aggression only among individuals with fewer AR(CAG) repeats (Geniole et al, 2019), which further supports our findings. In sum, these exploratory findings suggest that the conditional effects of testosterone on status-seeking motivation are moderated by androgen receptor-dependent pathways.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the current study, individuals with high androgen receptor sensitivity to testosterone (i.e., low AR(CAG)-repeat length), showed that testosterone (vs. placebo) increased motivation to compete when the competition progressed in those who had an unstable low status as well as in those who had a stable high status. A recent study in males demonstrated testosterone to promote aggression only among individuals with fewer AR(CAG) repeats (Geniole et al, 2019), which further supports our findings. In sum, these exploratory findings suggest that the conditional effects of testosterone on status-seeking motivation are moderated by androgen receptor-dependent pathways.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings contribute to other recent pharmacological studies using different behavioural paradigms, and suggest a causal role of testosterone in status-enhancing behaviors that depend on the social context. For instance increase preference for high status goods (Nave et al, 2018;Wu et al, 2017), increase willingness to punish a proposer who proposed an unfair offer in an Ultimatum Game, and increase willingness to reward those who propsed a fair offer (Dreher et al, 2016). Future studies could test if our findings of testosterone in individuals with unstable low social status also extend to behaviors in these paradigms.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations